تأثير منهج نفسي في تطوير المهارات النفسية و مهارة التصويب من القفز خارج القوس بكرة السلة للأعمار 17-18 سنة (Journal of the College of Basic Education, 2024)
The Correct Training Process Depends On The Best Modern Training Methods And Methods That Help Those In Charge Of Training To Implement Training Curricula And Development Programs That Seek To Reach The Highest Levels In Skill, Physical And Psychological PerformanceThis Is Also What We Apply In The Field Of Sports Training, That Is, Any Development Of Any Game To Reach The Required Level Requires Great Efforts In Preparing Scientific Programs And Plans, Theoretical And Practical Studies And Their Application, As Well As Removing The Problems Facing All The Game To Raise Its Level, Studies In The Field Of Sports Psychology Have Proven A Close Relationship To The Level Of Mental, Physical And Skill Abilities And Athletic Excellence.Therefore, It Is A Basis To Help The Researcher Develop Using A Psychological Approach Using Psychological Sessions, Where Mental And Skill Exercises Overlap As An Advantage In The Process Of Development In Skill Performance, Mastery And Development, Because They Work To Avoid Obstacles To The Player To The Details Of The Movement Parts And Try To Perform Correctly .